HEllo Can someone guide me with this? Consider the recurrence relation : an = (a(n-1))^3 * a(n-2)^2 Use logarithms to change (1) into a linear recurrence relation for (bn = log2(an)). Find such recurrence relation for {bn} Thank you
Follow Math Help Forum on Facebook and Google+
Originally Posted by qwerty321 HEllo Can someone guide me with this? Consider the recurrence relation : an = (a(n-1))^3 * a(n-2)^2 Use logarithms to change (1) into a linear recurrence relation for (bn =log2(an)). Find such recurrence relation for {bn} Thank you $\displaystyle a_n=a_{n-1}^3 \times a_{n-2}^2$ take logs (to base 2): $\displaystyle \log_2(a_n)=3\log_2(a_{n-1})+2 \log_2(a_{n-2})$ putting $\displaystyle b_n=\log_2(a_n)$ this becomes: $\displaystyle b_n=3b_{n-1}+2b_{n-2} $ .
View Tag Cloud